MANAGEMENT OF BLOOD HEMOGLOBIN LEVEL THROUGH THE CONSUMPTION OF LEMURU FISH STICK AS A SNACK FOOD IN YOUNG WOMEN SUFFERING FROM ANEMIA IN SMA NUSANTARA LUBUK PAKAM DISTRICT - Oppusunggu, Riris (Journal of Saintech Transfer, 2019)
Anemia is a condition where a person's hemoglobin (Hb) level in the blood is lower than normal. Adolescent girls are one group at risk of suffering from anemia. The main cause of anemia in young women is lack of iron intake, chronic blood loss during menstruation. The aim of this community service is to increase the knowledge of young women, especially those suffering from anemia, about the management of blood hemoglobin levels and to increase the knowledge of young women in understanding the procedure to make lemuru fish stick as a snack to increase the hemoglobin levels of young women in Nusantara Lubuk Pakam. The Community Service activities consists of counseling about anemia, counseling about lemuru fish sticks, examination of hemoglobin levels, demonstration of making products of lemuru fish sticks to increase blood hemoglobin levels to overcome anemia. The result of the activity is an increase in the knowledge of young women in understanding the procedure for making stick fish as a snack to increase hemoglobin levels.